A Model for Determining the Effective Thermal Conductivity of Porous Heterogeneous Materials - Bicer, Ayse; Kar, Filiz (Springer/Plenum Publishers, 2019)
In this study, an algebraic equation is shown for determining thermal conductivity coefficient of a porous heterogeneous solid material with two components. This equation was developed based on the porosity of the material, ratio, density and thermal conductivities of its components. This equation was applied to the waste EPS aggregate and samples with cement or gypsum mixed binders. Packaging waste EPSs were collected, decomposed to particles of 0-3mm diameter and mixed with each binder volumetrically in the ratios of 20%, 40%, 60% and 80% separately. Thermal conductivity coefficient of the samples was determined by using the hot wire method. The calculated values were 4.41% to 26.04% higher than the measured values in the samples with cement, and they were 5.79% to 15.62% higher than the measured values in the samples with gypsum. The equation was applied similarly to the samples with expanded clay and cement with pumice aggregates.
Keywords: Cement; Expanded polystyrene; Gypsum; Porous material; Thermal conductivity coefficient